PENGARUH PEMBERIAN MINUMAN AIR KUNYIT (CURCUMA LONGA) TERHADAP SKALA NYERI DISMENORE PADA REMAJA PUTRI DI DESA SUKASARI - Dwi Sagita Apriyani; Ningsih, Ningsih; Rina Puspita Sari (Nusantara Hasana Journal, 2022)
The incidence of menstrual pain in Indonesia reaches 60-70%, the incidence of primary type dysmenorrhea in Indonesia is around 54.89%, while the rest are dysmenorrhea sufferers with secondary type, where absenteeism from school ranges from 13-51% and 5% to 14 % of the absence is due to the severity of the symptoms that occur. So that menstrual pain is the main cause of absenteeism in adolescent girls. It is reported that more than 20% of pubertal adolescents are more likely to stay at home to rest and limit physical activity during menstrual pain. This hormonal imbalance will cause pain during the menstrual cycle. Pain during menstruation causes the patient's discomfort in carrying out daily physical activities so that it can interfere with the patient's productivity. There are several ways to relieve menstrual pain, one of which is the use of herbal medicines such as turmeric. Turmeric contains Curcumin. Curcumin works as an analgesic that will inhibit the release of excessive prostaglandins through the uterine epithelial tissue and will inhibit uterine contractions so that it will reduce menstrual pain. Princess in Sukasari Village. Methods: This research is a research that uses quantitative methods with a Quast Experimental research design. The design used in this research is one group pretest and posttest. In this study, we compared the results of the intervention for 3 days of drinking curcuma longa water in the Quasi Experimental group. The population in this study were all young women in the village of Sukasari, totaling 105 people. The sample needed in this study was 42 people based on the Lemeshow formula calculation. Based on the results of the Wilcoxon test, the value of sig. 2(2-tailed) is 0.000 (p < 0.05). The conclusion of this study is that based on the Wilcoxon test, the sig. (2-tailed) of 0.000 (p < 0.05) So it can be concluded that Ho is rejected and Ha is accepted, meaning that there is an effect of giving turmeric water (curcuma longa) to the dysmenorrhea pain scale in adolescent girls in Sukasari Village.